Treatment Preference For Patients With Chronic Obstructive Pulmonary Disease: A Review - Agung Rejecky; Erna Rochmawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic illness that requires regular treatment to relieve symptoms and reduce the frequency of relapses and the severity of exacerbations. Treatment options for COPD are pharmacological and non-pharmacological therapies, and patients can prefer the type of treatment. The inhaler is one of the options for pharmacological therapy, where there are several types of inhalers, including metered dose inhalers (MDI), soft mist inhalers (SMI) and dry powder inhalers (DPI). To date, there is no synthesis on the patient's preference of treatment for COPD. The review aimed to synthesize available evidence on patients' preferences for COPD treatment. Three databases, which include PubMed, Ebsco, and Scopus, were searched using terms related to "Patient Preference", "Preference Treatment", "Chronic Obstruction Pulmonary Disease", and "Chronic Airway Obstruction Disease". From the three databases, 2,757 articles were obtained and screened from a title with EndNote to remove duplication. The author and the team discuss the abstract and the full text to decide whether it meets the inclusion criteria. A total of 10 articles were included. We found patients prefer dry powder inhalers, spray inhalers, and relaxation by imagining a beautiful place as an option. The results of the literature review show that there are several preferences for COPD therapy; DPI inhalers are preferred because they are easy to use and have a low error rate. Abstrak: Penyakit Paru Obstruktif Kronik (PPOK) adalah penyakit kronis yang memerlukan pengobatan secara teratur untuk meredakan gejala, mengurangi frekuensi kekambuhan dan tingkat keparahan eksaserbasi. Pilihan pengobatan untuk PPOK adalah terapi farmakologis dan nonfarmakologis, dan pasien dapat memilih jenis pengobatan. Inhaler merupakan salah satu pilihan terapi farmakologi, dimana terdapat beberapa jenis inhaler diantaranya metered dose inhaler (MDI), soft mist inhaler (SMI) dan dry powder inhaler (DPI). Sampai saat ini, tidak ada sintesis pada preferensi pengobatan pasien dengan COPD. Tinjauan ini bertujuan untuk mensintesis bukti yang tersedia tentang preferensi pasien terhadap pengobatan PPOK. Tiga basis data yang meliputi PubMed, Ebsco, dan Scopus dicari menggunakan istilah-istilah yang terkait dengan “Preferensi Pasien”, “Pengobatan Preferensi”, “Penyakit Paru Obstruksi Kronis”, dan “Penyakit Obstruksi Jalan Napas Kronis”. Dari ketiga database tersebut diperoleh 2.757 artikel, dan disaring dari judulnya dengan EndNote untuk menghilangkan duplikasi. Penulis dan tim berdiskusi untuk menentukan abstrak dan teks lengkap untuk memutuskan apakah memenuhi kriteria inklusi. Sebanyak 10 artikel dimasukkan. Kami menemukan pasien lebih memilih inhaler bubuk kering (DPI), inhaler semprot (SMI), dan relaksasi dengan membayangkan tempat yang indah sebagai pilihan. Hasil tinjauan pustaka menunjukkan bahwa terdapat beberapa preferensi untuk terapi PPOK yaitu penggunaan inhaler DPI lebih disukai karena mudah digunakan dan memiliki tingkat kesalahan yang rendah.